EFEKTIVITAS Pelaksanaan Pemberdayaan Perempuan DAN DAMPAKNYA terhadap POLA Kesejahteraan Masyarakat - Didik Kusumahadi (Universitas Tribhuwana Tunggadewi, 2012)
Through this theory will know by easy cause factor and is difficult to strive enableness woman with aim to support prosperity of society, impact perceived to be limited knowledge aspect to program, activity followed, participation story level and benefit of program. Enableness of woman in so many this life sector is generally determined and influenced by difference background and equation of explained women through functional structural theory, power theory and status, communication theory of non verbal, theory of rape-prone and of rape free, and division of labor theory. . Elaborated also all activity which have been executed and attainment storey, level during execution of program enableness of woman. Target of research:1. to know and study the activities executed at program enableness of woman 2. to know and study impact execution of program enableness of woman to society. Result of research showed various activities have related to program enableness of woman among others is given to understand of passing training is important, group aid learn technology of fund. Affect from program enableness of big enough woman of this matter earn seen from is ever greater society capacities and ability in developing himself. Beside that awareness of society also gain strength for the importance of role of woman.